Ultra poor and asset transfer in Urban setting: Evidence from slums in Bangladesh - Ara, Jinnat; Hossain, Nusrat Zaitun; Das, Narayan Chandra; Bayes, Abdul (Wiley Online Library, 2022)
This article was published in The Journal of International Development [Copyright © 2016 John Wiley & Sons, Ltd.] and the definite version is available at: https://doi.org/10.1002/jid.3241 The Article's website is at: https://onlinelibrary.wiley.com/doi/full/10.1002/jid.3241